Abu Ishak Al-Syathibi (Ulasan Tentang Pemikiran Ijtihadnya Dalam Kitab Al-Muwafaqat) - Mohammad Ibnu Sulaiman Slamet (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2013)
Ijtihad is a one of legal instrument to establish the Islamic law. It is a important way to decide a law or toward new phenomenon that has not been described by law provisions texts such as Quran and Hadith. Al-Syathibi was a one of the scholars who were making ijtihad as a main study with lifting dimensions maqasid al-syaria as an alternative way of bringing forth ijtihad, Maqasid al-Shariah is a principal in al-Syathibi legal thought in which there is the concept of God as the goal of mashlahat. The thought al-Syathibi can be found in his book al-Muwafaqat fi Usul al-Sharia, as a monumental work in which includes a variety of legal thought al-Syathibi especially mashlahat concept to explain the meaning of sharia purposes (maqasid al-Shari'ah ) using logical and philosophical reasoning.